The conversion of β-carotene to vitamin A in adipocytes drives the anti-obesogenic effects of β-carotene in mice - Johana Coronel; Jianshi Yu; Nageswara Pilli; Maureen A. Kane; Jaume Amengual (Molecular Metabolism, 2022)
Objective: The β-carotene oxygenase 1 (BCO1) is the enzyme responsible for the cleavage of β-carotene to retinal, the first intermediate in vitamin A formation. Preclinical studies suggest that BCO1 expression is required for dietary β-carotene to affect lipid metabolism. The goal of this study was to generate a gene therapy strategy that over-expresses BCO1 in the adipose tissue and utilizes the β-carotene stored in adipocytes to produce vitamin A and reduce obesity. Methods: We generated a novel adipose-tissue-specific, adeno-associated vector to over-express BCO1 (AT-AAV-BCO1) in murine adipocytes. We tested this vector using a unique model to achieve β-carotene accumulation in the adipose tissue, in which Bco1−/− mice were fed β-carotene. An AT-AAV over-expressing green fluorescent protein was utilized as control. We evaluated the adequate delivery route and optimized cellular and organ specificity, dosage, and exposure of our vectors. We also employed morphometric analyses to evaluate the effect of BCO1 expression in adiposity, as well as HPLC and mass spectrometry to quantify β-carotene and retinoids in tissues, including retinoic acid. Results: AT-AAV-BCO1 infusions in the adipose tissue of the mice resulted in the production of retinoic acid, a vitamin A metabolite with strong effects on gene regulation. AT-AAV-BCO1 treatment also reduced adipose tissue size and adipocyte area by 35% and 30%, respectively. These effects were sex-specific, highlighting the complexity of vitamin A metabolism in mammals. Conclusions: The over-expression of BCO1 through delivery of an AT-AAV-BCO1 leads to the conversion of β-carotene to vitamin A in adipocytes, which subsequently results in reduction of adiposity. These studies highlight for the first time the potential of adipose tissue β-carotene as a target for BCO1 over-expression in the reduction of obesity.